Case report: Page kidney with multiple serosal effusions caused by bilateral spontaneous renal subcapsular hemorrhage - Wang, Leibo; Qiu, Zuze; Zhan, Shun; Shi, Guanyu; He, Wei; Cen, Zhuangding; Xu, Feng; Tian, Wu; Li, Daobing (Frontiers in Medicine, 2024)
Page kidney is caused by the perirenal or subcapsular accumulation of blood or fluid pressing on the renal parenchyma and is a rare cause of secondary hypertension. In this study, we report a case of Page caused by bilateral spontaneous subcapsular renal hematoma, the main manifestations of which were secondary hypertension, multiple serous effusions, and renal insufficiency. After admission, drug blood pressure control was ineffective. After bilateral perirenal effusion puncture and drainage were performed to relieve bilateral perirenal compression, blood pressure gradually dropped to normal, multi-serous cavity effusion (pericardial, thoracic, and abdominal effusion) gradually disappeared, and kidney function returned to normal. Secondary hypertension caused by Page kidney can be treated. When Page kidney is complicated with multiple serous effusions, the effect of antihypertensive drugs alone is poor, and early perineal puncture drainage can achieve better clinical efficacy.